Mechanisms of textual coherence, an applied approach: “Surat Al-Mulk” as an example. - Laouar, Amina (Journal of Human Sciences, 2024)
The text represents a structured linguistic unit whose elements combine certain relationships and junctions, and this is what makes it like a cohesive structure whose parts are interconnected and consistent with each other. Text grammar scholars have paid attention to these junctions and have tried to limit and classify them and study their functions in the language during its use. There are two types of them that take place on the surface of the text, which are: Grammatical connections, represented by “cohesion”, and some that are semantic or moral, represented by “coherence”.